Identifying a cell wall ideotype for increased soil carbon contents associated with Miscanthus cultivation - Holder, Amanda; Askew, Karen; Robson, Paul (Frontiers in Plant Science, 2026)
Dedicated biomass crops are widely accepted as an important part of decarbonising economies. Miscanthus is a leading dedicated biomass crop that embodies high yield with many co-benefits including soil carbon sequestration plus the benefits of perennial agronomy. Breeding programmes for Miscanthus are in their infancy but it is apposite to consider the potential for breeding improved soil carbon sequestration. We focussed on gross biomass inputs from leaf, roots and rhizome and examined both dry weight and cell wall composition as key factors that influence soil carbon sequestration. We measured lignin, cellulose, hemicellulose, carbon and nitrogen from all three tissues in different Miscanthus genotypes that had been grown in field plots and compared for soil carbon. There was a significant genotypic effect on most compositional traits from all three tissue types and composition also varied between tissue types. When combined with soil C data from field grown plants, lignin and lignin:N were shown to be useful predictive factors (along with soil depth) for total soil organic C and this combination of factors explained 86% of the model variance for Miscanthus derived soil C. Examples of trade-offs were observed but a high sequestering plant includes low root lignin and high belowground biomass.